Proteomic Profile of Flaxseed (Linum usitatissimum L.) Products as Influenced by Protein Concentration Method and Cultivar - Jarošová, Markéta; Roudnický, Pavel; Bárta, Jan; Zdráhal, Zbyněk; Bártová, Veronika; Stupková, Adéla; Lorenc, František; Bjelková, Marie; Kyselka, Jan; Jarošová, Eva; Bedrníček, Jan; Bohatá, Andrea (Foods (Basel, Switzerland), 2024)
The research is focused on the quantitative evaluation of the flaxseed (Linum usitatissimum L.) proteome at the level of seed cake (SC), fine flour-sieved a fraction below 250 µm (FF)-and protein concentrate (PC). The evaluation was performed on three oilseed flax cultivars (Agriol, Raciol, and Libra) with different levels of α-linolenic acid content using LC-MS/MS (shotgun proteomics) analysis, which was finalized by database searching using the NCBI protein database for Linum usitatissimum and related species. A total of 2560 protein groups (PGs) were identified, and their relative abundance was calculated. A set of 33 quantitatively most significant PGs was selected for further characterization. The selected PGs were divided into four classes-seed storage proteins (11S globulins and conlinins), oleosins, defense- and stress-related proteins, and other major proteins (mainly including enzymes). Seed storage proteins were found to be the most abundant proteins. Specifically, 11S globulins accounted for 41-44% of SC proteins, 40-46% of FF proteins, and 72-84% of PC proteins, depending on the cultivar. Conlinins (2S albumins) were the most abundant in FF, ranging from 10 to 13% (depending on cultivar). The second most important class from the point of relative abundance was oleosins, which were represented in SC and FF in the range of 2.1-3.8%, but only 0.36-1.20% in PC. Surprisingly, a relatively high abundance of chitinase was found in flax products as a protein related to defence and stress reactions.
Keywords: cultivar; flour; protein concentrates; flaxseed; proteomic profile; 11S globulin